Prestasi Belajar Pendidikan Agama Islam Ditinjau dari Persepsi Siswa Tentang Manajemen Kelas dan Kompetensi Guru di Sekolah Menengah Pertama - Syafitri, Aisyah; Sesmiarni, Zulfani (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
Effective classroom management and adequate teacher competence are two important factors that can influence student learning achievement. At SMPN 2 Tigo Nagari, the influence of these two aspects becomes even more relevant given the challenges of education in the region that require appropriate classroom management approaches and continuous teacher capacity building. Classroom management and teacher ability are two factors that influence the learning achievement of Islamic Religious Education (PAI) Class VIII students at SMPN 2 Tigo Nagari, Pasaman Regency. Good classroom management and the teacher's ability to convey information are very important to improve the quality of learning. Students' perceptions of teachers' abilities and classroom management also have an impact on students' motivation and understanding of lessons. Ultimately, student achievement is affected by this. The purpose of the quantitative correlation approach, which collects data through questionnaires and documentation, is to see how students' perceptions of teacher ability, classroom management, and their learning achievement contribute to each other. This study used a quantitative correlation approach and collected data through questionnaires and documentation. The results showed that classroom management (X1) and teacher professionalism (X2) have a significant relationship with students' learning achievement (Y). This is proven by the tcount value which is greater than the ttable (11.400 > 1.667) and the regression equation Y = 37.565 + 0.117X1. In addition, teacher competence and classroom management are simultaneously positively related to student learning achievement; the Fcount value is greater than Ftable (1142.415 greater than 3.13). This finding shows how important good classroom management and teacher ability are in improving student achievement.